Peran Sumber Energi Terbarukan dalam Penyediaan Energi Listrik dan Penurunan Emisi CO2 di Provinsi Daerah Istimewa Yogyakarta - Rahmat Adiprasetya Al Hasibi (Semesta Teknika, 2010)
Electrical energy modelling involving renewable energy was produce using LEAP software. The model is based on electrical energy demand, renewable energy potential, and development planning in Yogyakarta Province. Renewable energy sources that have been simulated in this model are solar energy, wind energy, and micro hydro energy. The model describes the role of renewable energy in producing electrical energy to supply electrical energy demand in Yogyakarta Province. Furthermore, the role of renewable energy in CO2 emission reduction has also been simulated by the model. By optimal development, renewble energy gives 11,86 % share of electrictiy demand and reduce CO2 emission by 11,62%.